2003
DOI: 10.1038/sj.thj.6200250
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of polycythemia vera patients treated with pipobroman as initial therapy

Abstract: From 1968 to 1993, 179 newly diagnosed patients with polycythemia vera (PV) were enrolled in a prospective study using pipobroman as first chemotherapy. Among them, 140 fulfilled the Polycythemia Vera Study Group criteria for PV, and 39 patients (22%) can be considered as idiopathic erythrocytosis (IE). Vascular events occurred in 10% of IE and 20% of PV patients and solid tumors in 7.7% of IE and 12.8% of PV patients. There were no differences between PV and IE patients with regard to progression to myelofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 24 publications
3
50
1
Order By: Relevance
“…In spite of these unfavorable prognostic features, the overall survival (91% at the median follow-up time of 5.84 years) compares favorably to that reported in many other studies [3][4][5][6]. Although we did not perform a prospective, randomized study and the median follow-up is shorter than 10 years, the wide use in our patients of lowdose ASA and the strong limitation of alkylating cytotoxic therapy may have contributed to this more favorable outcome and to an incidence of leukemic transformation in the lowest range of values reported in literature [4,[6][7][8]. Indeed, a French randomized study with very long followup has recently demonstrated a lower incidence of leukemic evolution and improved survival with the use of hydroxyurea compared to pipobroman [32].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In spite of these unfavorable prognostic features, the overall survival (91% at the median follow-up time of 5.84 years) compares favorably to that reported in many other studies [3][4][5][6]. Although we did not perform a prospective, randomized study and the median follow-up is shorter than 10 years, the wide use in our patients of lowdose ASA and the strong limitation of alkylating cytotoxic therapy may have contributed to this more favorable outcome and to an incidence of leukemic transformation in the lowest range of values reported in literature [4,[6][7][8]. Indeed, a French randomized study with very long followup has recently demonstrated a lower incidence of leukemic evolution and improved survival with the use of hydroxyurea compared to pipobroman [32].…”
Section: Discussionsupporting
confidence: 75%
“…Polycythemia vera (PV) is the most common chronic myeloproliferative neoplasm, with an annual incidence of 2.3 per 100,000 [1,2], a reported median survival of 10-15 years [3][4][5][6] and an overall mortality of 3.5 per 100 person/year [5]. Thrombotic complications are the main cause of morbidity and mortality, occurring in more than one third of patients and causing 35-45% of deaths [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18]20,48,49 A study on 831 patients with PV and ET followed for a median time of about 10 years provided evidence that life expectancy of PV patients is reduced when compared with that of the general population, whereas the survival of patients with ET is not significantly shortened. 18 A study from Mayo Clinic including 322 patients with ET followed for a median time of 13.6 years confirmed these data on survival in the first decade of disease and showed that survival became significantly worse thereafter.…”
Section: Life Expectancy In Polycythaemia Vera and Essential Thrombocmentioning
confidence: 99%
“…With regard to the survival, PMF is associated with a substantial reduction in life expectancy, [6][7][8][9][10][11][12][13][14] and ET affects more the patients' quality of life than their survival, whereas PV is associated with both a substantial morbidity and a certain reduction in the patients' life expectancy. [15][16][17][18] Because of this, prognostic studies in the MPDs have been carried out primarily in PMF. In the last years, however, attention is increasingly being paid to the identification of prognostic factors in ET and PV, primarily focused on the risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%